STUDENTS’ PERCEPTION ON THE USE OF PREACHING METHOD AND CALL MEDIA IN TEACHING ENGLISH: A Descriptive Research - Jubaidah; Amin, Bahrun; Ardiana (Journal of Computer Interaction in Education, 2018)
This research aimed to investigate students’ perception on the use of preaching method and Computer Assisted Language Learning (CALL) media in teaching English at seventh semester students English Department Muhammadiyah University of Makassar. This study applied a descriptive qualitative study. The data gained through open-ended interview and process with question interview that was present in paper, data reduction, and coding technique. The data was gained from seventh semester students at English Department Muhammadiyah University of Makassar. Based on the findings, it finds that students gave the positive perception toward the use of preaching method and Computer Assisted Language Learning (CALL) Media in teaching English to measure the effectiveness of the method and the media to support their English skills or knowledge. Moreover, the students claimed that they have many advantages during the implementation of preaching method and CALL media. This study also found that this strategy was needed to be improved by the lecturers in terms of giving instruction, observing the class and evaluating the implementation of preaching method and CALL media in English class